Physics of matter - King, George C. (Hoboken: John Wiley & Sons., 2023)
"Matter is any substance that has mass and takes up space. It can exist in several different forms known as phases and a phase is a form of matter that has a relatively uniform chemical composition and physical properties. Phases include the three familiar ones: solids, liquids, and gases; as well as more exotic states of matter such as plasmas, superfluids, etc"--
Atoms, the constituents of matter -- The forces that bind atoms together -- Thermal energy of atoms and molecules -- Kinetic theory of gases: transport processes -- Real gases -- The First Law of Thermodynamics -- The Second Law of Thermodynamics -- Solids -- The elastic properties of solids -- Thermal and transport properties of solids -- Liquids -- Liquid crystals.
Includes index.
Keywords: Matter -- Properties; Matter -- Textbooks